Genealogia das políticas proibicionistas sobre drogas no Brasil, 1970-1990 - Neves, Anderson Souto (2015)
In the late 1970 it emerges in Brazil a drug policy supported by the provisions of the 1961 UN Single Convention, which designates the ban on the consumption and trade of certain substances labelled as improper for consumption. Several conferences were convened in the course of the 20th century which contributed to the establishment of the prohibitionist paradigm about drugs as a real regime embodied in Brazil in standardisation and safety devices as the laws No. 6,368/76, law nº/02 and law 10,409 11,343/06. These devices assist the governmentality of the population with regard to the consumption of substances labeled as drugs, such as cocaine, heroin, marijuana and others. These substances are liable by the prohibitionist political model by the rise of criminality, the most diverse social problems, and the problems inherent to Public Health. Such assumptions are discursive practices manifests of a moralist, often without the support of competent scientific research. In this way, this study aims for making a prohibition genealogy, analyzing the incorporation of their precepts for the practices governmentality in Brazil during the decades of 1970 and 1990.